Denaturalization and denationalization in comparison (France, the United Kingdom, the United States). (May 2017) - Weil, Patrick
Denaturalization and denationalization were once much more common among western democracies. From 1906 till 1968, the United States of America, France and the United Kingdom denationalized their citizens by hundreds and thousands, for fraud or illegality during the process of naturalization, for dual citizenship, or for banal default of loyalty. In a context of a 'war against terror' we are now seeing an apparent return to the past – with the resuming of denationalization policies and provisions. However, the previous restriction imposed through courts and judicial bodies on the power to denaturalize in the USA, France and the UK, the international recognition of citizenship as the most important human right, the transformation of nationality and the acceptance of dual citizenship, and the impact and meaning of citizenship in a republic explain why, while being hotly debated and highly supported by the majority of citizens, denationalization has resumed only symbolically in the USA and France, if not in the UK.